Experience of Malaysia's economic reform and lessons learned - Bouchoul, Said; Djermoun, Souad; Gaoui, Maamar (Finance and Business Economies Review, 2020)
Enter The study examined the experience of Malaysia in the field of economic reform by selecting a group of the most important activities (manufacturing, services, foreign direct investment, human development). The reflection of these reforms was expressed by analyzing a range of economic indicators (including per capita GDP, Competitiveness, ease of doing business, human development index, etc.) that highlight Malaysia's performance by each activity from 1990 to 2017. The study found that human capital played a key role in the success of reforms in Malaysia, Human and transform it To energy and competitive advantage directed to effective investments is the result of the belief that the secret of its growth and growth lies in the minds of their children and their sleeves, which reflected positively on all indicators of economic and social activities in the country